Comparative Genomics and Proteomic Analysis of Four Non-tuberculous Mycobacterium Species and Mycobacterium tuberculosis Complex: Occurrence of Shared Immunogenic Proteins - Gcebe, Nomakorinte; Michel, Anita; Gey van Pittius, Nicolaas C.; Rutten, Victor (Frontiers in Microbiology, 2016)
The Esx and PE/PPE families of proteins are among the most immunodominant mycobacterial antigens and have thus been the focus of research to develop vaccines and immunological tests for diagnosis of bovine and human tuberculosis, mainly caused by Mycobacterium bovis and Mycobacterium tuberculosis, respectively. In non-tuberculous mycobacteria (NTM), multiple copies of genes encoding homologous proteins have mainly been identified in pathogenic Mycobacterium species phylogenically related to Mycobacterium tuberculosis and Mycobacterium bovis. Only ancestral copies of these genes have been identified in nonpathogenic NTM species like Mycobacterium smegmatis, Mycobacterium sp. KMS, Mycobacterium sp. MCS and Mycobacterium sp. JLS. In this study we elucidated the genomes of four nonpathogenic NTM species, viz Mycobacterium komanii sp. nov., Mycobacterium malmesburii sp. nov., Mycobacterium nonchromogenicum, and Mycobacterium fortuitum ATCC 6841. These genomes were investigated for genes encoding for the Esx and PE/PPE (situated in the esx cluster) family of proteins as well as adjacent genes situated in the ESX-1 to ESX-5 regions. To identify proteins actually expressed, comparative proteomic analyses of purified protein derivatives from three of the NTM as well as Mycobacterium kansasii ATCC 12478 and the commercially available purified protein derivatives from Mycobacterium bovis and Mycobacterium avium was performed. The genomic analysis revealed the occurrence in each of the four NTM, orthologs of the genes encoding for the Esx family, the PE and PPE family proteins in M. bovis and M. tuberculosis. The identification of genes of the ESX-1, ESX-3 and ESX-4 region including esxA, esxB, ppe68, pe5 and pe35 adds to earlier reports of these genes in nonpathogenic NTM like M. smegmatis, Mycobacterium sp. JLS and Mycobacterium KMS. This report is also the first to identify esxN gene situated within the ESX-5 locus in M. nonchromogenicum. Our proteomics analysis identified a total of 609 proteins in the six PPDs and 22 of these were identified as shared between PPD of M.bovis and one or more of the NTM PPDs. Previously characterized M tuberculosis/M. bovis homologous immunogenic proteins detected in one or more of the nonpathogenic NTM in this study included CFP-10 (detected in M. malmesburii sp. nov. PPD), GroES (detected in all